Pengaruh Daya Tarik E-Commerce Lazada, Promosi Penjualan Dan Brand Ambassador Terhadap Keputusan Pembelian Gen Z (Di Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas) - Debi Gusnita; Yeni Del Rosa (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to see how the influence of Lazada's E-commerce Attraction, Sales Promotion and Brand Ambassador on Gen Z's purchasing decisions. The independent variables in this study are Attraction, Sales Promotion and Brand Ambassador while the dependent variable is Purchase Decision. The type of research used is quantitative descriptive. This study was conducted using the saturated sample method or total sampling where the researcher took the entire population as a sample. The population in this study were D3 and S1 management students class of 2024 at Dharma Andalas University. The respondents numbered 135 people, after distributing the questionnaire the researcher got 83 respondents who passed the criteria. The results of this study indicate that: (1) Lazada's e-commerce attraction has a positive and significant effect on purchasing decisions, (2) Sales promotions have a positive and significant effect on purchasing decisions, (3) Brand Ambassador has a positive and significant effect on purchasing decisions, (4) Lazada's e-commerce attraction, sales promotions, and brand ambassadors simultaneously have a positive and significant effect on purchasing decisions.